THE STUDY OF THE INFLUENCE OF THE TYPE Ol CHEESE ON THE ORGANOLEPTIC AND PHYSICO- CHEMICAL PROPERTIES OF PIZZA - A. V. Borisova; A. V. Barsukova; O. O. Egorova (Современная наука и инновации, 2022)
This article explores the effect of various cheeses in pizza recipes on the physicochemical and organoleptic characteristics of finished products.